Pemasangan Lampu Panel Surya Sederhana sebagai Solusi Penerangan yang Ramah Lingkungan di Taman Rukun Warga - Cania Atika Tabina; Desty Endrawati Subroto; Alfitho Dea Nova; Ilham Mubarok; Zia’ul Fatwa Andini Yusuf (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Outdoor lighting, such as in community parks, plays a crucial role in supporting community activities at night while enhancing safety and comfort. Unfortunately, traditional electricity usage is often inefficient and has negative environmental impacts due to carbon emissions from fossil fuel-based power plants. This study aims to implement solar panel technology as an environmentally friendly lighting solution in Taman RukunWarga, located in Kelurahan Bendung, Kecamatan Kasemen, Kota Serang. The methods applied in this study include site surveys, assembly of the solar-powered lighting system, and performance analysis after installation. The lighting system consists of a 30 Wp solar panel, a battery (accumulator), a solar charge controller, a 12V 20W DC LED light, and other supporting components. The results show that this system can provide adequate and even lighting for the park area while being energy-efficient. One of the main advantages of this system is its ability to reduce operational costs by using renewable solar energy and requiring minimal maintenance. Additionally, the implementation of this solar-powered lighting system has increased public awareness of the importance of utilizing renewable energy and reducing carbon emissions in the surrounding environment. Overall, the installation of this solar-powered lighting system has proven to be a sustainable, energy-efficient, and environmentally friendly alternative for meeting lighting needs in community parks. This system not only reduces dependence on fossil fuels but also contributes to efforts to mitigate negative environmental impacts. By utilizing solar energy, this system serves as a positive example of the application of renewable energy technology in daily life, while helping to create a cleaner and healthier environment for the community.